Advancing cancer therapy with custom-built alternating electric field devices - Isobel Jobson; Nguyen T. N. Vo; Edward Kujawinski; Chris Denning; Snow Stolnik; Veeren M. Chauhan; Frankie Rawson (Bioelectronic Medicine)
Abstract Background In glioblastoma (GBM) therapy research, tumour treating fields by the company Novocure™, have shown promise for increasing patient overall survival. When used with the chemotherapeutic agent temozolomide, they extend median survival by five months. However, there is a space to design alternative systems that will be amenable for wider use in current research. Therefore, we sought to establish a custom-built alternating electric field device to investigate the effect of electrode design on the responsiveness of cancer cells to this therapy. Methods A 96-well microtiter plate modified with an electrode array was fabricated to investigate its application as an in vitro alternating electric field device. This was initially performed with patient-derived GCE 31 and GIN 31 cell lines found in the core and invasive margin of the GBM tumour, respectively. We sought to establish the effect of the application of low-intensity (3 V/ cm) electric fields with an application duration of 4—48 h, using intermediate frequency (300 kHz) alternating currents (AC). To demonstrate that electric fields were entering the cell, GCE 31 and GIN 31 cells were treated with the inorganic, non-conductive zinc oxide (ZnO) nanoparticles (NP), previously demonstrated to enhance the efficacy of TTFs. After a 4-h exposure to NP, cells were then exposed to alternating electric fields or currents and their metabolic activity was assessed. To better understand how the position and morphology of cells can affect cell therapy responsiveness to alternating electric fields or currents, GBM results were compared to those from the semi-adherent brain tumour cell line, D425. Results Contrary to previous findings, there was no significant difference between the GIN 31 and GCE 31 cells exposed to alternating electric fields or currents treated with or without NP compared to cells untreated and unstimulated. D425 cells exposed to alternating electric fields exhibited a pronounced metabolic increase (1.8-fold), while those exposed to alternating electric currents with or without ZnO had a reduced metabolism relative to the untreated control. Conclusions The initial hypothesis for the lack of effect of electrical stimulation on the adherent cells was that, due to only a single pair of electrodes being used, the proportion of cells that were in the correct orientation for electric field effects was limited. However, the dramatic shift in cell behaviour of the semi-adherent cells shows that cell morphology plays an important role in the responsiveness of cancer cells to AC electric fields. This study highlights the lack of understanding of the complex mechanisms by which electric fields exert effects on cancer cells. We propose that, for the therapy to be enhanced for patients, research should first focus on the underlying mechanisms of action, specifically on how individual cancer cell types respond to this therapy.